Spontaneous mid-trimester rupture of unscarred uterus - K, Kala; Kumar, Jayashree Ashok; I, Rathipriya; Kamda, Jyoti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Spontaneous uterine rupture in early pregnancy and in unscarred uterus is an extremely rare event. It carries high maternal mortality and morbidity rate. We report a case of G2P1L1 with prior vaginal delivery who came with 21 weeks of gestation with pain abdomen, spotting per vagina and loss of fetal movements. During laparotomy entire amniotic sac was seen in peritoneal cavity. A rent of 6 to 7 cm was seen in left lateral wall of uterus which was repaired. Spontaneous rupture should be considered in women with acute pain abdomen even in absence of any risk factors regardless of gestational age and parity.